MENGENAL ALAM SEKITAR UPAYA MENINGKATKAN LITERASI SAINS SISWA MELALUI PEMBELAJARAN KONTEKSTUAL (CTL) DI SD/MI - Siti Mutmainah; Umi Farihah; Indah Wahyuni (SIRAJUDDIN : Jurnal Penelitian dan Kajian Pendidikan Islam, 2025)
This study aims to describe efforts to improve students’ science literacy through contextual learning that connects science materials with the natural environment surrounding elementary school students. The research employed a descriptive qualitative approach and was conducted at SDN Mangli 1 Jember and MIN 3 Jember. Informants included the school principals, science teachers, students’ parents, and students in grades IV and V. Data were collected through in-depth interviews, observation, and documentation, and analyzed thematically using the Miles and Huberman model with source and technique triangulation. The findings revealed that efforts to improve science literacy were carried out by actively involving students in observation, simple experiments, and reflection on natural phenomena in their surroundings. Contextual learning was implemented through the integration of CTL (Contextual Teaching and Learning) principles such as inquiry, learning community, and authentic assessment. The school environment was utilized as a learning resource that encouraged student engagement and the development of science process skills. Learning activities that connected subject matter to real-life contexts effectively fostered curiosity, critical thinking skills, and environmental awareness. This study recommends that teachers consistently apply locally contextualized learning as a strategy to enhance science literacy at the elementary level. Furthermore, involving parents and the community is essential to support more meaningful science learning for students.